ANAEROB THRESHOLD UNTUK CABANG OLAHRAGA SPRINT ATLETIK - Arif Ramadani; Young Sitompul; Ade Irmawan; Suryadi Damanik; Mesnan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of anaerobic threshold (AT) as the main physiological indicator in improving athletic sprint performance and to identify the effectiveness of high-intensity training interventions on metabolic adaptation and speed endurance. The issue raised focuses on the limitations of applying the AT concept in high-intensity but short-duration sprint sports. This study uses a secondary quantitative design through a systematic literature review based on PRISMA guidelines. The analysis was conducted on studies that reported the relationship between AT, repeated sprint training (RST), sprint interval training (SIT), and sprint performance indicators (peak speed, reaction time, and recovery between sprints). The results of the study show that RST and SIT interventions tailored to individual physiological thresholds significantly improve AT, ventilation efficiency, and muscle energy recovery capacity, thereby improving the stability of repeated sprint performance. The increase in AT is proven to be positively correlated with the ability to maintain speed in repeated sprints and reduce power degradation due to lactate accumulation. The study's conclusion emphasizes that AT is an important parameter in the planning and evaluation of physiology-based sprint training. Theoretically, these findings reinforce the metabolic adaptation model in sports physiology, while practically providing guidelines for coaches in designing measurable and efficient training programs. Further research is recommended to develop field-based AT measurement protocols and explore the direct causal relationship between AT changes and specific sprint performance.